2016
DOI: 10.1002/14651858.cd000938.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour at or near term for suspected fetal macrosomia

Abstract: 29 per 1000 (13 to 65) M oderate 29 per 1000 29 per 1000 (13 to 65)* The risk in the intervention group (and its 95% conf idence interval) is based on the assum ed risk in the com parison group and the relative effect of the intervention (and its 95% CI).CI: Conf idence interval; RR: Risk ratio; OR: Odds ratio;GRADE Working Group grades of evidence High quality: We are very conf ident that the true ef f ect lies close to that of the estim ate of the ef f ect M oderate quality: We are m oderately conf ident in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 24 publications
2
86
0
7
Order By: Relevance
“…Induction of labor for impending macrosomia has been proposed to prevent complications. A recent meta-analysis [2] including 4 trials and 1,190 women shows that induction of labor for suspected fetal macrosomia results in a lower birth weight and fewer birth fractures and shoulder dystocias, without increasing the cesarean section and instrumental delivery rates. This has put the spotlight on improving prediction of excessive fetal weight before labor onset for proper counseling and decision-making.…”
mentioning
confidence: 99%
“…Induction of labor for impending macrosomia has been proposed to prevent complications. A recent meta-analysis [2] including 4 trials and 1,190 women shows that induction of labor for suspected fetal macrosomia results in a lower birth weight and fewer birth fractures and shoulder dystocias, without increasing the cesarean section and instrumental delivery rates. This has put the spotlight on improving prediction of excessive fetal weight before labor onset for proper counseling and decision-making.…”
mentioning
confidence: 99%
“…The results of randomized trials conducted in 19 centers in France, Switzerland and Belgium have demonstrated that labor induction between 37 and 39 weeks of pregnancies with LGA fetuses diagnosed by ultrasound (above the 90th percentile for the gestational age) reduces the risk of shoulder dystocia and the related neonatal morbidity compared with expectant management [23]. However, the number needed to prevent one neonatal clavicular fracture during labor induction was 60 [24]. There were no significant differences in the percentage of caesarean sections, but early induction of labor improved the chance for vaginal delivery.…”
Section: Suspected Large-for-gestational-age Fetusesmentioning
confidence: 99%
“…Induction of labor in pregnancies with suspected LGA fetuses decreases the need for caesarean section and difficult operative delivery [24]. However, the exact size of the fetus must be estimated for the procedure to be efficient and burdened with the least risk of complications.…”
Section: Suspected Large-for-gestational-age Fetusesmentioning
confidence: 99%
“…However, most of the studies found higher rate of successful delivery after induction. The reason for which cesarean section was Mishanina et al [48] 2014 Systematic review and meta-analysis Decreased Hofmeyr and Gulmezoglu [92] 2001 Systematic review Decreased Wood et al [93] 2014 Meta-analysis Decreased Gulmezoglu et al [47] 2006 Systematic review Decreased Gulmezoglu et al [94] 2012 Systematic review Decreased Sanchez Ramos et al [29] 2003 Systematic review Decreased Alfirevic et al [76] 2014 Systematic review Decreased Alfirevic et al [95] 2000 Systematic review Decreased Boulvain et al [30] 2008 Systematic review Decreased Vogel et al [35] 2013 Systematic review Decreased Crowley [96] 2000 Systematic review No difference Boulvain et al [73] 2016 Systematic review Not clear Guerra et al [26] 2009 Secondary analysis Decreased Cheng [97] 2008 RCT Decreased Koopmans et al [98] 2009 RCT Decreased Pennel et al [99] 2009 RCT Increased Bhutto et al [100] 2013 RCT Nil Hermus et al [101] 2009 Cohort No difference Marry et al [37] 2015 Cohort Decreased Yeast et al [102] 1999 Cohort Decreased Nooh et al [103] 2005 Retrospective Decreased Dubline et al [19] 2000 Cohort Increased Johnson et al [104] 2003 Cohort Increased Verhoeven et al [22] 2012 Case control Increased…”
Section: Discussionmentioning
confidence: 99%
“…Induced women had significantly higher cesarean rate than the spontaneous group [5,72]. However, Boulvain et al did not get any clear risk of c-section after induction [73]. Sometime it was observed that there are no significant differences in CS rates between the groups of vaginal misoprostol or dinoprostone after induction [74].…”
Section: Tripathy and Babymentioning
confidence: 99%